Comparative Analysis of National Parks in the Sahel Region, Wildlife Protection in the Sahel Countries - Hillender, Tímea (Journal of Central and Eastern European African Studies, 2026)
The Sahel region is characterized by semi-arid conditions and fragile ecosystems. The area faces extreme climate variability, recurrent droughts, and accelerating soil erosion. Communities are also exposed to political instability, armed conflicts, and economic crises. This combination creates a highly vulnerable environment where environmental, social, and security challenges reinforce one another, making the Sahel one of the most fragile regions in the world. In this context, national parks play a role that extends far beyond traditional conservation. They are not only biodiversity reserves but also potential instruments for stability, sustainable livelihoods, and community engagement. By protecting ecosystems, supporting local populations, and offering opportunities for tourism and income generation, they can contribute to resilience in a region under constant pressure. This analysis examines the national parks of seven Sahel countries—Mauritania, Mali, Burkina Faso, Chad, Benin, Niger, and Nigeria—in a comparative way. The focus is placed on institutional capacity, management practices, security issues, and the degree of community participation. Special attention is also given to the role of tourism as both an economic driver and a tool for social cohesion. By comparing the countries, common patterns as well as major differences emerge. These insights help explain why similar ecological corridors may lead to very different developmental pathways, depending on governance, resources, and community involvement.